2013
DOI: 10.1093/cvr/cvt049
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin deficiency dampens the pro-atherogenic effect of uraemia

Abstract: The data suggest that OPN promotes development of uraemic atherosclerosis possibly by changing the phenotype of vascular smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
2
11
1
Order By: Relevance
“…Similarly, a recent study by Ghosh et al also did not detect increased fibrosis in this model [24]. Furthermore, previous studies in our group [8, 25, 26] have established that kidney function after 5/6 NX does not deteriorate progressively with time (up to 1 year) in C57Bl6/J mice. It is therefore possible that 5/6 NX on a C57Bl6/J background merely reflect early stages of kidney injury, incl.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, a recent study by Ghosh et al also did not detect increased fibrosis in this model [24]. Furthermore, previous studies in our group [8, 25, 26] have established that kidney function after 5/6 NX does not deteriorate progressively with time (up to 1 year) in C57Bl6/J mice. It is therefore possible that 5/6 NX on a C57Bl6/J background merely reflect early stages of kidney injury, incl.…”
Section: Discussionsupporting
confidence: 83%
“…Ten-to-thirteen weeks old mice were subjected to 5/6 nephrectomy (NX), as previously described [7, 8] to induce mild to moderate uremia. Briefly, 5/6 nephrectomy was achieved in a 2-step operation.…”
Section: Methodsmentioning
confidence: 99%
“…In experimental uremia plasma OP was increased and correlated positively with aortic atherosclerosis [48]. In our study we confirmed that plasma OP level is markedly increased in patients on regular HD but it does not relate to VS parameters.…”
Section: Discussionsupporting
confidence: 81%
“…To our surprise, the gene expression analyses showed no uremia-mediated effects on expression of the SMC genes in the carotid control arteries in wt or Apoe −/− mice (apart from Tagln , which was downregulated by NX in control arteries in wt mice). This is in contrast to previous data in aortic SMCs 16, 18, 25, 26 , in which uremia altered mRNA expression of classical SMC marker genes. The gene expression differences observed in the previous vs the present study may thus relate to the different vascular beds examined, i.e.…”
Section: Discussioncontrasting
confidence: 99%